Friday and Robinson: life on Esperanza Island. - Tournier, Michel; Tournier, Michel; Martin, David Stone (New York Knopf, 1972)
A new approach to the Robinson Crusoe story which explores Robinson's psychological as well as physical experiences and introduces a new twist--Friday eventually becomes master of Robinson.
Translation of Vendredi; ou, La vie sauvage, a version for children of the author's Vendredi; ou, Les limbes du Pacifique.
Keywords: Survival -- Fiction